Analisis Proses Bisnis dan Penerapan Manajemen Strategis pada PT Optik XYZ - Alianto, Hendra (ComTech: Computer, Mathematics and Engineering Applications, 2011)
That optic business is increasingly mushrooming followed by a decrease in market share, forces Optik XYZ to have competent management strategies to achieve a strong position in competing in similar industry. Therefore a study was conducted to provide a structured and systematic analysis of management strategies required by Optik XYZ. Stages of study were initiated by data collection from interviews, literature studies and field studies, followed by qualitative and quantitative analysis and implementation of management strategies. The study generated a formulation of management strategy proper for Optik XYZ. Management strategies formulated in this study can help carrying out the company's activities in decision making, so that the business processes run optimally.